A new, quick, effective and minimally invasive treatment technique applied to ingrown toenails - Şenol, Zafer; Gülşen, Taygun (The European Research Journal, 2022)
Objectives: Existing surgical and conservative treatment techniques applied to ingrown toenails remain controversial. In this study, a new minimally invasive technique for the treatment of ingrown toenails is described which was found to provide rapid healing and effective results. Methods: The presented study includes 39 patients with ingrown toenails treated with the newly developed technique. The technique is a minimally invasive procedure in which a half groove-shaped piece obtained from the intravenous drip set plastic was placed between nail and dermis and fixed on the nail. Results: The patients treated with this technique were followed up after one week, one month and six months. According to six-month follow-up results of the patients, achievement rate of the presented technique was found to be quite high at 80%. Conclusions: This new technique has many advantages compared to existing ingrown toenail treatment methods. It was revealed that this method is very effective and successful by not requiring dressing, ensuring low pain, rapid recovery from the first day of the treatment, uninterrupted return to daily life, and low recurrence rate. One of the most important advantages of the technique is that it ensures high patient satisfaction by providing good functional and aesthetic results.